Indications for partial superficial parotidectomy for benign parotid gland tumors using the retrograde approach - Suzuki, Masahiro (Fukushima J Med Sci, 2020)
A recent systematic review and meta-analysis suggest that retrograde parotidectomy is a safe procedure with no significant difference in facial nerve paralysis rates when compared to anterograde parotidectomy. The aim of the current study was to establish indications for partial superficial parotidectomy using the retrograde approach. To this end, the two surgical techniques were compared in terms of postoperative facial nerve paralysis, tumor size, location of the tumor, and surgical time. For tumor diameters of 30 mm or less, mean surgical time in the retrograde parotidectomy group was significantly shorter than in the anterograde parotidectomy group (p < 0.05). Our study indicates that retrograde parotidectomy may be more effective than anterograde parotidectomy for partial superficial parotidectomy for benign parotid tumors of 30 mm or less.